SUSTAINABLE FLOATING ARCHITECTURE PROTOTYPE AS ENERGY EFFICIENCY METHODS IMPLEMENTATION IN INDONESIA - Rani Yuni Wulandari; Stephanus Wirawan Dharmatanna; Sitti Awalia Dewi Permatasari; Diandra Aprilia Judiono; Ismail Salam (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2021)
Indonesia has a coastline of 54,716 km whereas, the second-longest coastline in the world after Canada. However, coastal architectural planning is limited to high-traffic areas, such as recreation areas or harbors. Meanwhile, local coastal settlement areas developed without proper planning. It goes with the local people's lack of understanding for decent settlement also, the bad habits that have been carried out from generation to generation, like throwing garbage into the sea where contribute to the marine pollution index increment. Therefore, it is necessary to develop sustainable coastal settlement architectural planning. Therefore, we tried to make a floating house architectural plan for the coastal area with a prototype idea that applies the energy efficiency concept. Where combines a qualitative explorative approach to the coastal buildings concept and quantitative energy studies with computer simulations. Emphasized within this study is the utilization of marine waste also renewable energy technologies such as waves, solar heat, wind, and other natural resources applications in buildings. Whereas capable of contributing to reducing the marine pollution index and adequate to create energy sources independently. Which later on feasibly implemented as an architectural planning reference for coastal areas in the world. Keywords: Coastal Architecture, Floating House, Sustainable Architecture, Energy Efficiency Architecture, Indonesia